Environmental and health implications of liquid waste from the stone carving industry: Case study in Sedayu Village, Magelang, Central Java, Indonesia - Sutaryono Sutaryono Sutaryono; Rezyana Budi Syahputri; Tuti Susilowati; Teguh Setyadi; Purwanti; Sukamsi; Dhanik Ernawati; Mohamad Samsudin; Taufiq Hidayat; Hastin Dyah Kusumawardani; Ina Kusrini (Jurnal Teknologi Laboratorium)
Sedayu Village in Magelang Regency is a hub for stone carving craftsmanship, generating liquid waste that poses potential environmental contamination and health hazards. This study aims to analyze the quality of liquid waste produced and evaluate environmental health risks. Implementing the composite sampling method, liquid waste samples were taken from industrial outlets and released into the Keranjang River. The analyzed parameters include TSS, pH, BOD, COD, nitrate, chromium, and phenol. Laboratory results revealed concentrations of TSS at 200 mg/L, BOD at 50 mg/L, COD at 100 mg/L, nitrite at 1 mg/L, hexavalent chromium at 0.1 mg/L, and phenol at 0.05 mg/L, all exceeding environmental quality standards. The health risk assessment, conducted using the Environmental Health Risk Assessment (EHRA) method, the RQ values for nitrite (0.039), chromium (0.129), and phenol (0.006) are below 1, indicating low immediate risk, chronic exposure could lead to bioaccumulation and long-term health effects such as methemoglobinemia and carcinogenic risks. Thus, immediate intervention is essential. As a mitigation strategy, the study recommends waste management interventions. The proposed WWTP should include activated carbon filtration to remove heavy metals and advanced oxidation processes for organic pollutants like phenol.